Health Care Workers’ Perspectives on the Barriers and Facilitators to Digital Health Technology Use to Support Symptomatic Cancer Diagnosis in Southern Africa: Qualitative Study - Kirsten D Arendse; Sarah Day; Bothwell Takaingofa Guzha; Tasleem Ras; Valerie Anne Sills; Natalie Tegama; Jennifer Moodley; Fiona M Walter; Suzanne E Scott (Journal of Medical Internet Research)
Abstract BackgroundDespite improvements in early cancer diagnosis worldwide, morbidity and mortality in Southern Africa continue to rise owing to challenges with funding, sociocultural beliefs, and health care access. Digital health (“eHealth”) has the potential to expand access to health care, particularly to remote communities. However, few studies explored the use of eHealth to support symptomatic cancer diagnosis in Southern Africa. ObjectiveThis study explored the barriers and facilitators to eHealth use by health care workers (HCWs) to support the management of people with symptoms of possible breast, cervical, or colorectal cancer in South Africa and Zimbabwe. MethodsWe conducted semistructured in-depth interviews with HCWs (n=56) who managed people with symptoms of possible cancer. Interviews explored the barriers and facilitators to eHealth use and attitudes toward further adoption of eHealth. Interview schedules were guided by the sociotechnical theory, a model “designed to address the socio-technical challenges involved in design, development, implementation, use, and evaluation of eHealth.” The interviews were audio-recorded and transcribed. We used the framework method to analyze the data and developed themes that encompassed patterns and meaning in the data to answer the research question. ResultsThe median age of participants was 44 (IQR 34‐53) years, 38 (68%) were female, and most were nurses (n=34, 61%) or doctors (n=18, 32%). Four core themes were developed: (1) “the lack of reliable infrastructure hindered eHealth use among HCWs”; (2) “the use of personal mobile devices increased eHealth access at the expense of patient privacy and personal cost”; (3) “information, workflow integration, and access”; while eHealth improved access to information, many tools were already in use, were poorly integrated into workflow, and disrupted consultations; and (4) “digital health is expanding whether we like it or not,” which describes a spectrum of attitudes toward digital health, ranging from enthusiasm to resistance but willingness to adapt to those completely against its use. Themes from the workshops were concordant with the in-depth interview findings. ConclusionsTo capitalize on the potential benefits of eHealth use among HCWs, such as to support early cancer diagnosis, infrastructural challenges must be addressed, and tools designed to meet user needs and be integrated into clinical workflow. As in many other resource-constrained settings, significant improvements in development are required for the value of eHealth to be realized in Southern Africa. Additionally, where resources such as electricity are limited, their use for eHealth needs to be weighed against use for other priorities such as operating ventilators. Furthermore, energy production in these regions is largely reliant on burning fossil fuels, and thus, the use of eHealth tools risks contributing negatively to climate change. The findings of this study can be used to guide future eHealth design or implementation strategies that are more contextually suitable.